2014
DOI: 10.1002/14651858.cd003078.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Double bag or Y-set versus standard transfer systems for continuous ambulatory peritoneal dialysis in end-stage kidney disease

Abstract: Double bag or Y-set versus standard transfer systems for continuous ambulatory peritoneal dialysis in end-stage kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Over these years, two important changes were made in the care of PD patients, namely the use of the disconnect system since 1994 and the use of biocompatible solutions since 2005. Several previous reports have suggested that PD device advancement from a single bag to twin-bag systems has reduced the incidence of touch contamination causing PDassociated peritonitis (2). Our data showed that twin-bag systems have had a favorable effect on the incidence of PD-associated peritonitis, as was also reported by van Esch et al (18).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Over these years, two important changes were made in the care of PD patients, namely the use of the disconnect system since 1994 and the use of biocompatible solutions since 2005. Several previous reports have suggested that PD device advancement from a single bag to twin-bag systems has reduced the incidence of touch contamination causing PDassociated peritonitis (2). Our data showed that twin-bag systems have had a favorable effect on the incidence of PD-associated peritonitis, as was also reported by van Esch et al (18).…”
Section: Discussionsupporting
confidence: 86%
“…As previously identified, changing from single-bag to twin-bag systems specifically reduced infection with Staphylococcus sp. (2,18), as well as PD-associated peritonitis, at a global level. Pseudomonas aeruginosa accounted for 13.2% of PD-associated peritonitis episodes between 1995 and 1999 in Hong Kong, and for 5.3% of cases between 2003 and 2006 in Australia (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies identified peritonitis as an independent risk factor for patients and technique survival in PD patients [6,7,13]. The impact of peritonitis changed largely due to the decrease in the peritonitis rate through the use of the double-bag or Y-set [17]. Furthermore, of the number of effective peritonitis treatments increased after the widespread application of the ISPD guidelines [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Die Peritonitisrate ist in den letzten Jahren und Jahrzenten kontinuierlich auf zuletzt 0,06-1,66 Ereignisse pro Patientenjahre -in Abhängigkeit vom Zentrum und Land -zurückgegangen [4][5][6][7][8]. Dies wurde durch wichtige technische Entwicklungen wie die Einführung der Doppelkammer-und Y-Systeme sowie den Einsatz von biokompatiblen Lösungen möglich [9][10][11]. Aufgrund dieser Zahlen empfiehlt die International Society for Peritoneal Dialysis (ISPD) in der aktuellen Leitlinie eine Peritonitisrate von unter 0,5 Ereignissen pro Jahr (kleiner als 1 Ereignis pro 24 Monate) [12].…”
unclassified